Lambs with white muscle disease and selenium content of soil and meadow hay in the region of Kars, Turkey - Beytut, E; Karatas, F; Beytut, E (Elsevier Sci Ltd, 2002)
[Abstract Not Available]
Keywords: bambs; white muscle disease; selenium; soil; meadow hay